The Effect of Anti-Tuberculosis Drugs (ATT) Routine on Blood Profiles and Nutritional Status of Children at Ulin Hospital, Banjarmasin - Khairiyadi, Khairiyadi; Sitompul, Putriana Br.; Putra, Nataniel Hadi; Panghiyangani, Roselina (Jurnal Kedokteran Brawijaya, 2025)
Tuberculosis (TB) is an infectious disease caused by the rod-shaped bacterium Mycobacterium tuberculosis (M. TB). TB primarily affects the lung parenchyma (pulmonary TB), but the bacterium can also infect other organs, leading to extrapulmonary TB. Anti-Tuberculosis Drugs (ATT) are a crucial component of TB treatment. However, the use of ATT is associated with side effects, the most common being anaemia and thrombocytopenia. This study aims to determine the effect of ATT on routine blood profiles and the nutritional status of pediatric patients with pulmonary TB and glandular TB at Ulin Regional Hospital, Banjarmasin. This analytical observational study employed a cross-sectional design. A total of 52 pediatric patients with pulmonary TB and glandular TB at Ulin Regional Hospital, Banjarmasin, were selected using a non-probability total sampling approach. The Wilcoxon test revealed a significant effect of ATT therapy on nutritional status, as indicated by a p-value of 0.000. ATT therapy results in changes in routine blood profiles and significant improvements in the nutritional status of pediatric patients with pulmonary TB and glandular TB. The significant changes in the routine blood profile are haemoglobin level and monocytes level which increased after ATT therapy. The average leukocytes, neutrophils, lymphocytes and Erythrocyte Sedimentation Rate (ESR) level decreased significantly after ATT therapy, while Platelet counts remained unchanged.